Improved Oral Hygine as A Result of Successful Toothbrushing Intervention in a Restricted Community Islamic Boarding School - Pindobilowo1 , Dwi Ariani2 , Nadia Shabrina Amalia3 , Taufan Bramantoro4 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Introduction: Brushing teeth is an important thing to do since it is one of the factors that affect oral hygiene, especially to remove plaque on the teeth.1 The ability to brush teeth properly and correctly is a fairly important factor in maintaining dental and oral health, especially in adolescence.5 The purpose of study to explain the differences in plaque scores before and after toothbrushing training using Bass technique in adolescents Method: The sample were 100 students aged 12-15 years old in grades 7, 8 and 9. This study design was experimental quasi and using a pre-test and post-test after 7 days to determine the difference in plaque scores before and after the training. The plaque index method that used to examine oral hygine was Patient Hygiene Performance (PHP). Comparison between plaque scores before and after training evaluated using Wilcoxon test. Result: Examination of PHP index before training shows 81 samples (81%) in poor criteria, then most subjects undergoes improvement after training. There were 94 samples (94%) experienced decrease or improvement in plaque score whilst 6 samples (6%) did not show improvement after training. Median of plaque score before training was 4.3 (0.2-5 (SD=0.502)) afterwards improved to 2.2 (0-4.8 (SD=0.496)). Wilcoxon test obtained a value of p<0.05 which was 0.000. Conclusion: There were significant differences in plaque scores before and after toothbrushing training using Bass technique.